IMPLEMENTATION OF PROGRESSIVE WEB APPS-BASED CLICK PROFILE ON SOCIAL MEDIA - Amin, Ruhul; Jodi, Setiawan (LPPM Nusa Mandiri, 2021)
Instagram as one of the social media that has active users with a high number of users is an example of the use of social media as promotional media. However, limitations on Instagram by not allowing placing a